1995
DOI: 10.3109/10428199509051718
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Dysregulation in Chronic Graft Versus Host Disease

Abstract: Copyright: Qian et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License 3.0 (CC BY 3.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. ABSTRACT Allogeneic hematopoietic stem cell transplantation is a well-established treatment for many malignant and non-malignant hematological disorders. As a frequent complication in up to 50% of all patients, graft-versus-host disease is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
1
8

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 13 publications
1
44
1
8
Order By: Relevance
“…19,22 On the other hand, other studies favor a Th1-driven mechanism of cGVHD in both murine and human systems. [23][24][25] However, the current study could not detect any significant difference in IL-4 or IFN-g production from CD4 þ T cells between patients with and without cGVHD. Although the reason for the discrepancy in the results between the previous reports and this study is currently unknown, it might be related to the difference in the severity of cGVHD examined.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…19,22 On the other hand, other studies favor a Th1-driven mechanism of cGVHD in both murine and human systems. [23][24][25] However, the current study could not detect any significant difference in IL-4 or IFN-g production from CD4 þ T cells between patients with and without cGVHD. Although the reason for the discrepancy in the results between the previous reports and this study is currently unknown, it might be related to the difference in the severity of cGVHD examined.…”
Section: Discussioncontrasting
confidence: 44%
“…20 In addition, several reports have demonstrated that type 2 cytokines are associated with cGVHD, 21,22 whereas other studies favor the significance of Th1 balance in cGVHD. [23][24][25][26] In this study, we analyzed the cytokine production of T cells in the chronic phase of patients who underwent allo-HSCT and found that IL-4-producing CD8 þ T cells are closely associated with cGVHD.…”
Section: Gvhd; Hsct; Cytokinesmentioning
confidence: 99%
“…6,7 There have been reports that TNF-␣ is also related to the development of chronic GVHD (cGVHD). 8,9 The clinical features of cGVHD are similar to those of several autoimmune diseases, and can include autoantibody formation. [10][11][12][13] IL-10 was originally defined as a cytokine able to alter the balance of mouse Th1 and Th2 activity.…”
mentioning
confidence: 99%
“…In patients with chronic GVHD, both the serum IL-10 level and IL-10 production from mononuclear cells have been shown to decrease after stimulation. [12][13][14] After stimulation with lipopolysaccharide, M-CSF-induced macrophages produce large amounts of IL-10 instead of IL-12. 15 Recent reports have shown that M-CSF induced DCs with IL-4 in a culture from human cord blood, and that these DCs produced high amounts of IL-10, but not IL-12, a pattern similar to that seen in M-CSF-induced macrophages.…”
Section: Discussionmentioning
confidence: 99%